Formulation and characterization of nanomicelles loaded with azithromycin for improved solubility - Pradip Rajput; Atul Kaushik (The Bioscan, 2026)
The objective of the present investigation was to prepare nano-micelles loaded with azithromycin for improving its solubility and bioavailability. Nanomicelles were prepared using Soluplus as the surfactant and thin film method.